P15 Cyclosporine a is protective against oxidative stress in adult but not in immature isolated cardiomyocytes. (21st March 2018) - Lewis, MJ; Hall, J; Keylock, L; Lin, H; Summers, K; Suleiman, MS
Abstract : *These authors contributed equally to the project The vulnerability of intact rat hearts to ischaemia and reperfusion injury changes during post-natal development with 14 days old being most resistant. The mechanism for this is multifactorial, but one significant element is the changing characteristics of the mitochondrial permeability transition pore (MPTP). We investigated the effect of oxidative stress and Ca2+ loading on cardiomyocyte viability in cell suspension throughout development with or without MPTP inhibition. Ventricular cardiomyocytes were isolated enzymatically from 14 (n=4), 28 day old (n=3) and adult rat heart (n=3). These cardiomyocytes were incubated with 0.5 mM H2O2 and 3 mM Ca2+ (simulated reperfusion) in the presence or absence of 2 µM Cyclosporine A (CsA). Cardiomyocytes incubated in normal buffer were used as control. Cardiomyocyte viability (assessed using trypan blue) and morphology was monitored every 30 min for 2 hours. There was a time-dependent decrease in viability in all age groups. However, this effect was more marked in 14 day old compared to adult and 28 day old cardiomyocytes. In the adult group, CsA significantly improved cardiomyocyte viability at all time points (at 120 min, 76%±7.4 vs 53%±5.3). No protective effect was seen in 14 (22%±12.7 for CsA vs 10%±6.6 injured control) or 28 day old cardiomyocytes (55%±7.9 for CsA vs 33±5.4 for injured control). Unlike intact adult heart, the resistance of isolated cardiomyocytes to simulated reperfusion injury increases from 14 days of age to adulthood. The finding that CsA does not confer protection in the younger age group could be due to excessive injury or due to changes in MPTP sensitivity.